Survei Gross Motor Skill Activities Siswa Kelas I SD Negeri 6 Demuk Kecamatan Pucanglaban Kabupaten Tulungagung Tahun 2024 - Agnes Puji Darmawan; Slamet Junaidi; Moh. Nur Kholis (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research is to find out a basic picture of the level of development Gross Motor Skill Activities Grade IV students at SDN 6 Demuk, Pucanglaban District, Tulungagung Regency. Because this is another research, this research was carried out on a smaller scale at SDN 6 Demuk, Pucanglaban District, Tulungagung Regency. It is hoped that this research can serve as a guide for other researchers to conduct similar research at the national level. The reason for choosing elementary school students over preschool children is because elementary school students are easier to manage than preschool students. Thus, selecting younger and more beneficial primary school students. Gross Motor Skill Activities (GMSA) is a basic movement pattern to support more complex movements in sports and daily activities. Where elementary school age children, both PAUD, Kindergarten and Elementary School, really enjoy moving, whether playing sports or daily activities. In this research the author used a descriptive quantitative approach and research techniques used survey methods. Where all students will be evaluated with Test of Gross Motor Development-2 (TGMD-2). From a sample of 40 students consisting of 23 male students and 17 female students from 2 classes A and B. The following data was obtained: 23 male students obtained a percentage of 80.38%, 17 female students obtained a percentage of 80.14%, where these results can be categorized as very high for male students and high for female students. So it can be concluded that the level of development Gross Motor Skill Activities class students at SDN 6 Demuk, Pucanglaban District, Tulungagung Regency for the 2023/2024 Academic Year can be said to be high.